Butelase 1 is an Asx-specific ligase enabling peptide macrocyclization and synthesis - Qiu, Yibo (2015)
Proteases are ubiquitous in nature, whereas naturally occurring peptide ligases, enzymes catalyzing the reverse reactions of proteases, are rare occurrences. Here we describe the discovery of butelase 1, to our knowledge the first asparagine/aspartate (Asx) peptide ligase to be reported. This highly efficient enzyme was isolated from Clitoria ternatea, a cyclic peptide-producing medicinal plant. Butelase 1 shares 71% sequence identity and the same catalytic triad with legumain proteases but does not hydrolyze the protease substrate of legumain. Instead, butelase 1 cyclizes various peptides of plant and animal origin with yields greater than 95%. With Kcat values of up to 17 s(-1) and catalytic efficiencies as high as 542,000 M(-1) s(-1), butelase 1 is the fastest peptide ligase known. Notably, butelase 1 also displays broad specificity for the N-terminal amino acids of the peptide substrate, thus providing a new tool for C terminus-specific intermolecular peptide ligations.